ANALISIS TERHADAP HILANGNYA HAK POLITIK BAGI TERPIDANA KORUPSI DITINJAU DARI HAK ASASI MANUSIA - Mirza Hilmi Fahlevi, Achmad Hariri (Madani Legal Review, 2021)
As we understand, the problem that occurs is how the revocation of political rights for convicted corruption perpetrators in Indonesia and what consequences will occur if the implementation of the revocation of political rights for corruption convicts from the point of view of human rights. The purpose of this study is to find out that the revocation of political rights for convicts of corruption from the point of view of human rights based on Court Decision Number 537 K/Pid.Sus/2014 An. Inspector General Djoko Susilo. The method used is a normative juridical research method, which is based on the decision of the Supreme Court, books on corruption and the severe opinions of legal experts. The revocation of political rights for convicts of corruption is not a form of violation of human rights, because convicts of corruption are mostly state officials whose duties and functions are to protect and help the community.